Hasil, Kualitas Fisik Polong dan Biji Beberapa Genotipe Kacang Tanah menurut Ragam Lengas Tanah pada Fase Generatif - Rahmianna, Agustina Asri; Purnomo, dan Joko (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2018)
Drought stress during generative stage affected pod yield, yield components, seed and pod qualities of groundnut (Arachis hypogaea L.). The reseach was carried out to assess the effect of drought stress at various soil water availabilities during generative stage on pod yield, pod and seed physical qualities. The experiment was conducted at Muneng Experimental Farm, Probolinggo District during July-October 2012. Five genotypes were arranged in a RCB design, with 3 replicates. The replications were nested into four treatments of soil water availability (0-100, 0-85, 0-70,0-55 days after sowing/DAS). The pods were harvested at 102 days after sowing. The result showed that the shorter the water availability, the lower the leaf relative water content, pod and seed water contents, number of mature pods, seed size, and intact seeds weight. Pod yield reduced when water was available upto 55 DAS only. Turangga variety had the highest pod yield (1.626 ton ha-1) with low pod and seed physical qualities. GH-51 yielded in 1.076 ton ha-1 with superior pod and seed physical qualities. Despite of its lowest pod yield (0.964 ton ha-1), J-11 produced the same pod and seed physical qualities as GH 51 did. ICGV 86590 was superior on its pod yield (1.338 ton ha-1) with low pod and seed physical qualities. Kancil variety did not perform any superiority.Keywords: intact seeds, leaf relative water content, pod moisture content, seed moisture content